Low noise, tunable Ho:fiber soliton oscillator for Ho:YLF amplifier seeding. (17th May 2016) - Li, Peng; Ruehl, Axel; Bransley, Colleen; Hartl, Ingmar
Abstract: We present a passively mode-locked, tunable soliton Ho:fiber ring oscillator, optimized for seeding of holmium-doped yttrium lithium flouride (Ho:YLF) amplifiers. The oscillator is independently tunable in central wavelength and spectral width from 2040 to 2070 nm and from 5 to 10 nm, respectively. At all settings the pulse energy within the soliton is around 800 pJ. The soliton oscillator was optimized to fully meet the spectral requirements for seeding Ho:YLF amplifiers. Its Kelly sidebands are located outside the amplifier gain spectrum, resulting in a train of about 1 ps long pedestal-free pulses with relative intensity noise of only 0.13% RMS when integrated from 1 Hz to Nyquist frequency.